Study protocol: primary healthcare transformation through patient-centred medical homes—improving access, relational care and outcomes in an urban Aboriginal and Torres Strait Islander population, a mixed methods prospective cohort study. Issue 9 (29th September 2022) - Butler, Danielle; Clifford-Motopi, Anton; Mathew, Saira; Nelson, Carmel; Brown, Renee; Gardner, Karen; Turner, Lyle; Coombe, Leanne; Roe, Yvette; Gao, Yu; Ward, James
Abstract : Introduction: For over 40 years, Aboriginal and Torres Strait Islander Community-Controlled Health Services (ACCHS) in Australia have led strategic responses to address the specific needs of Aboriginal and Torres Strait Islander populations. Globally, there has been rapid growth in urban Indigenous populations requiring an adaptive primary healthcare response. Patient-centred medical homes (PCMH) are an evidenced-based model of primary healthcare suited to this challenge, underpinned by principles aligned with the ACCHS sector—relational care responsive to patient identified healthcare priorities. Evidence is lacking on the implementation and effectiveness of the PCMH model of care governed by, and delivered for, Aboriginal and Torres Strait Islander populations in large urban settings. Method and analysis: Our multiphased mixed-methods prospective cohort study will compare standard care provided by a network of ACCHS to an adapted PCMH model of care. Phase 1 using qualitative interviews with staff and patients and quantitative analysis of routine primary care health record data will examine the implementation, feasibility and acceptability of the PCMH. Phase 2 using linked survey, primary care and hospitalisation data will examine the impact of our adapted PCMH on access to care, relational and quality of care, health and wellbeing outcomes and economic costs. Phase 3 will synthesise evidence on mechanisms for change and discuss their implications for sustainability and transferability of PCMHs to the broader primary healthcare system Ethics and dissemination: This study has received approval from the University of Queensland Human Research Ethics Committee (2021/HE00529). This research represents an Aboriginal led and governed partnership in response to identified community priorities. The findings will contribute new knowledge on how key mechanisms underpinning the success and implementation of the model can be introduced into policy and practice. Study findings will be disseminated to service providers, researchers, policymakers and, most importantly, the communities themselves.